International trade, location and wage inequality in China - Songhua Lin (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2003)
Models of economic geography predict that transportation costs directly affect demand for goods and the supply of intermediate inputs. One of the reasons that international trade is concentrated in the coastal provinces of China is that they have lower transportation costs in transporting goods to other countries than do provinces in the interior. This paper examines the relationship between the provincial wage rate and each province's access to international markets, and to suppliers of intermediate inputs. A gravity equation is first estimated to construct these `market access' and `supplier access' variables. In the second stage, the effect of market access and supplier access on the wage rate is estimated. It is found that about one quarter of the provincial wage differences in the coastal provinces and 15 per cent of the wage differences in the interior provinces can be explained by these economic geography variables.
Keywords: F14; O53; R12; 330; trade; China; regional disparities; wage rates; Außenwirtschaft; Regionale Disparität; Regionale Lohnstruktur; China